2017
DOI: 10.1186/s12884-017-1320-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for postpartum depression among Chinese women: path model analysis

Abstract: BackgroundPostpartum depression causes harm to both mothers and infants. The purpose of this study was to find out several potential risk factors, and to identify the intrinsic interrelationships between factors and postpartum depression by constructing a path model. The results of this study may help to control the increasing incidence of maternal postpartum depression.MethodsThe study was based on a sample of mothers from a cross-sectional study which was set up at 4 weeks after a mother had childbirth and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
66
3
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(80 citation statements)
references
References 26 publications
8
66
3
3
Order By: Relevance
“…This tradition includes a set of practices involving prescribed diet, clothing and other cautions that must be followed during the first month after delivery. Numerous studies have revealed "doing the month" have positive influence on the recovery of the mother and successful adaptation to maternal role [21,22]. Not following this ritual could lead to postpartum difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…This tradition includes a set of practices involving prescribed diet, clothing and other cautions that must be followed during the first month after delivery. Numerous studies have revealed "doing the month" have positive influence on the recovery of the mother and successful adaptation to maternal role [21,22]. Not following this ritual could lead to postpartum difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that the prevalence of PPD is about 10% in developed countries [ 6 ] and nearly 20% in developing countries [ 7 ]. The magnitude of PPD is 6.7% in China [ 8 ], 21% in Japan [ 9 ], 11 to 16% in India [ 10 ], and 39.4% in Bangladesh [ 11 ]. In Africa, the prevalence of PPD is 18.7% in Kenya [ 12 ], 7% in Ghana [ 13 ], and 9.2% in Sudan [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The stress process model was developed by Peirlin and colleagues [45] and consists of three main conceptual domains: the source of stress (stressor) domain, which includes life events and chronic life strains; the mediators domain, which includes any mediators of stress that have an ability to mediate the impact of stressfull situations such as social support and coping styles; and the manifestation of the stress or stress outcomes as various mental disorders. This stress process model has been tested both in pregnant [46] and postnatal [47] populations in China for antenatal and postnatal specific depression. For the current study we considered direct stressors including sociodemographic factors, obstetric and psychosocial factors and mediating factors such as social and personal resources (social support, partner support, personal coping abilities).…”
Section: Introductionmentioning
confidence: 99%